The Improperness Of Present Tense In Jonathan Liandi’s Empetalk - Muhammad Rayhan Ramadhan; Ambalegin Ambalegin (Prosiding, 2023)
This research aimed to discover the improperness of present tense in Jonathan Liandi’s Empetalk. In this research, qualitative descriptive used as the research method. The researchers used the script of interview from Jonathan Liandi’s Empetalk as the data source. In collecting the data, the method was observation and the technique was non-participant. Meanwhile, in analyzing the data, the method was identification and the technique was competence in comparing. The utterances from the script of interview which were taken as the data were analyzed narratively. The researchers used the theory of (Hewings, 2013) to discover the improper of present tense. The researchers discovered 7 utterances based on the findings. spoken that show the improper use of present tense. There were the improperness of verb used, and the improperness of adverb of frequency used.